Performance evaluation of silver-based nanomaterials enhanced with fullerenes as cathodes for flexible zinc-air batteries - Chipoco Haro, Danae Ariana (2020)
Metal-air batteries are characterized by a high energy density with relatively simple and safe chemistry which makes them suitable for many applications, especially the ones requiring flexibility. These energy storage devices consist of one metal electrode, an air electrode, which enhance the oxygen evolution and oxygen reduction reactions (OER and ORR, respectively), and an electrolyte. The air electrode is lighter than most metal electrodes present in batteries; therefore, these batteries have a high energy density. However, the most critical problem this technology faces involves the air electrode design, especially because of the requirement of a bifunctional catalyst for OER and ORR. Here, the enhancement of the catalytic activity of silver nanoparticles impregnated on carbon nanotubes (CNT) for OER and ORR using polyhydroxy fullerene (PHF) is discussed, as well as the methodology needed for an experimental demonstration of this hypothesis. This study contributes to the worldwide efforts of the scientific community to develop flexible, small and light batteries and may be a starting point in the use of PHF for this application.